The joint project on improved management and utilization of dark clay soils in Ethiopia - Retrospects and prospects - Abebe, M.; Jutzi, S.C. (IBSRAM, 1989)
Presents retrospects and prospects of the joint project on improved management and utilization of dark clay soils in Ethiopia. Discusses the contributions of partner institutions, the propspects for future collaboration, and the need for strengthening the foundation for the generation of advanced technological elements. Outlines the interinstitutional and interdisciplinary task-sharing framework of the joint project in which networks can play a significant role in research and extension.